Experimental investigation of external fan cowl separation for compact nacelles in windmilling scenarios - Sabnis, Kshitij; Boscagl, Luca; Babinsky, Holger; MacManus, David G.; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The slim fan cowl profiles used for ultra-high bypass ratio aircraft engines are designed considering off-design operating conditions, such as engine windmilling during take-off climb out or during cruise. The current paper describes wind tunnel experiments studying how incoming Mach number and engine mass-flow rate influence the aerodynamics governing external fan cowl flow separation in both these windmilling scenarios. A transonic region may form on the forebody surface if the engine becomes inoperative during take-off climb out, with peak Mach number up to 1.2. The subsequent adverse pressure gradient can separate the local boundary layer, resulting in flow separation which originates near the highlight and a more uniform fan cowl pressure distribution. Meanwhile, engine shut down during cruise results in a large supersonic region on the external fan cowl surface which terminates in a normal shock wave. When the Mach number of this shock exceeds about 1.35, a closed separation bubble develops, which causes up to a four-fold increase in the boundary-layer thickness downstream of the shock wave.